The Proactionary Imperative - Fuller, S. author. aut Link
IX, 153 p.
Keywords: The Proactionary Imperative debates the concept of transforming human nature, including such thorny topics as humanity's privilege as a species, our capacity to 'play God', the idea that we might treat our genes as a capital investment, eugenics and what it might mean to be 'human' in the context of risky scientific and technological interventions.